Evaluation of the Canine Intervertebral Disc Structure in Turbo Spin Echo-T2 and Fast Field Echo-T1 Sequences in Magnetic Resonance Imaging - Kunze, Katarina; Stein, Veronika Maria; Tipold, Andrea (Frontiers in Veterinary Science, 2019)
In the current study the hypothesis should be proven that T1 weighted Fast Field Echo (FFE) sequence is a useful method to visualise intervertebral disc degeneration respectively changes of the expected disc appearance. Medical records of 208 dogs were reviewed and images of 781 intervertebral discs were evaluated by two blinded examiners using a modified Pfirrmann classification system in two MRI sequences: FFE and Turbo-Spin-Echo T2-weighted sequence (T2W). The patients were allocated to three categories based on body conformation: (1) brachycephalic and chondrodystrophic breeds, (2) non-chondrodystrophic and non-brachycephalic breeds with a body weight of less than 25 kg, and (3) non-chondrodystrophic and non-brachycephalic breeds with a body weight greater or equal 25 kg. In brachycephalic and chondrodystrophic dogs 340 intervertebral discs were evaluated, the majority of them presented a mild change of the normal disc structure, 53% in the FFE sequence and 41% in T2W images. High discrepancies were observed between mild and moderate degeneration: in the FFE-sequence 15% (n = 50) of the discs had signs of mild degeneration, whereas in T2W the same discs were graded as moderately degenerated. In non-chondrodystrophic and non-brachycephalic breeds under 25 kg body weight 320 intervertebral discs were assessed. In the FFE-sequence 52% (n = 166) of the intervertebral discs were judged as having a mild degeneration. In contrast, these same discs were graded as healthy discs (22%), mildly degenerated (33%), moderately degenerated (37%) and severely degenerated (8%) in T2W. In non-chondrodystrophic and non-brachycephalic breeds greater or equal 25 kg 121 intervertebral discs were assessed. The grading was equal in 43%, but differed in one grade (47%) and in two grades (10%) between the two sequences. In both sequences intervertebral disc herniations were equally well diagnosed. The Kappa coefficient revealed a high discrepancy between the two MRI-sequences. In conclusion, FFE cannot replace the well established T2W sequence for grading disc degeneration.